2019
DOI: 10.21276/apalm.2410
|View full text |Cite
|
Sign up to set email alerts
|

A Clinico-Hematological Study of Cases of Leucoerythroblastic Reaction

Abstract: A Clinico-Hematological Study of Cases of Leucoerythroblastic Reaction With this backdrop, the present study was planned to study the hematological changes, especially peripheral blood smear (PBS) findings in LER cases. Materials and methods Ethics: Prior approval was taken from Institutional Ethics Committee before commencing the study. A written informed consent was taken from patients or guardian/ parents as applicable. Methodology: The present study was an observational, cross-sectional study conducted ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…12 In this study, maximum number of cases was seen in 21-30 years age group with male to female ratio of 1.1:1. Shubha HV et al 13 and Waghmare T et al 14 also observed maximum cases in 3 r d decade in their study with no significant sex distribution. On Bone marrow examination, non-neoplastic conditions were seen in 65% cases while neoplastic lesions were seen in 35% cases (Table 2).…”
Section: Discussionmentioning
confidence: 55%
“…12 In this study, maximum number of cases was seen in 21-30 years age group with male to female ratio of 1.1:1. Shubha HV et al 13 and Waghmare T et al 14 also observed maximum cases in 3 r d decade in their study with no significant sex distribution. On Bone marrow examination, non-neoplastic conditions were seen in 65% cases while neoplastic lesions were seen in 35% cases (Table 2).…”
Section: Discussionmentioning
confidence: 55%